Cryptococcal osteomyelitis of the femur: A case report and review of literature - Zainal, A.I; Wong, S.L; Pan, K.L.; Wong, O.L; Tzar, M.N (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Fungal osteomyelitis is a rare opportunistic infection. It exhibits some clinical and radiological similarities to several other bone pathologies. A diagnostic delay may result in significant increase in morbidity. We report a case of a 37-year-old man with underlying hypogammaglobulinaemia presented with isolated cryptococcal osteomyelitis of the femur.